PHYTOCHEMICAL ANALYSIS OF CYRTANTHUS OBLIQUUS BULBS FROM THE INFORMAL STREET MARKET OF KWAZULU-NATAL, SOUTH AFRICA - Mahlangeni, Nomfundo T.; Moodley, Roshila; Jonnalagadda, Sreekanth B. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Cyrtanthus obliquus is a medicinal plant commonly known by the locals in South Africa as Umathunga. It is used in traditional SouthAfrican medicine for the treatment of scrofula, chronic coughs and headaches and is also used to prepare the popular decoction known as Imbiza.Materials and methods: The secondary metabolites from C. obliquus bulbs were extracted using solvent extraction techniques, isolated usingcolumn chromatography and identified using spectroscopic techniques. The antioxidant potential of the isolated compounds was determined by the2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and the ferric reducing antioxidant potential (FRAP) assay.Results: The extracts yielded four homoisoflavonoids, 5,7-dihydroxy-6-methoxy-3-(4ꞌ-methoxybenzyl)chroman-4-one, 5,7-dihydroxy-3-(4ꞌ-hydroxybenzyl)chroman-4-one,5,7-dihydroxy-6-methoxy-3-(4ꞌ-methoxybenzylidene)chroman-4-one and 5,7-dihydroxy-3-(4ꞌ-hydroxybenzylidene)chroman-4-one. An unusual 3-β-glucopyranosyl-22,27-dihydroxy-lanosta-8-ene was also isolated from the bulbs. Theantioxidant studies showed that 3-benzylchromanones have better activity than 3-benzylidenechromanones.Conclusion: Four homoisoflavanones namely 5,7-dihydroxy-6-methoxy-3-(4ꞌ-methoxybenzyl)chroman-4-one; 5,7-dihydroxy-6-methoxy-3-(4ꞌ-hydroxybenzyl)chroman-4-one and two 5,7-dihydroxy-6-methoxy-3-(4ꞌ-methoxybenzylidene)chroman-4-one; 5,7-dihydroxy-3-(4ꞌ-hydroxybenzylidene)-chroman-4-one were obtained from Cyrtanthus obliquus.